Predicting total phosphorus levels as indicators for shallow lake management - Mohammadi, Babak (Ecological indicators, 2019)
The discusser thanks the authors for investigating the ability of modified random forest algorithm to predicting total phosphorus levels as indicators for shallow lake management. The abilities of machine learning techniques such as optimization algorithms today have been well documented in engineering sciences. In this discussion, the discusser has tried to clarify the process of the paper of “Predicting total phosphorus levels as indicators for shallow lake management”(doi: https://doi.org/10.1016/j.ecolind.2018.09.002). The discusser would like to call attention to some important points, which may be taken into consideration by the authors and other potential researchers.